PrEP acceptability and initiation among women engaged in sex work in Uganda: Implications for HIV prevention. (February 2022) - Witte, Susan S.; Filippone, Prema; Ssewamala, Fred M.; Nabunya, Proscovia; Bahar, Ozge Sensoy; Mayo-Wilson, Larissa Jennings; Namuwonge, Flavia; Damulira, Christopher; Tozan, Yesim; Kiyingi, Joshua; Nabayinda, Josephine; Mwebembezi, Abel; et al.
Summary: Background: Women engaged in sex work (WESW) are disproportionately affected by HIV. In Uganda, HIV prevalence among WESW is estimated at 37%, accounting for 18% of all new infections in the country. WESW experience poverty, gender-based violence, and other issues that reduce their power and limit their ability to negotiate condom use. Female-controlled strategies, including pre-exposure prophylaxis (PrEP), may afford women more transmission protection, but barriers to access and use persist. This cross-sectional study examined baseline PrEP acceptability and initiation among WESW recently enrolled in a randomized clinical trial in Uganda to test the impact of a combination HIV risk reduction and economic empowerment intervention on sexual risk outcomes (clinicaltrials.gov, NCT03583541). Methods: A total of 542 WESW from 19 high HIV-prevalent geographical areas were enrolled in the Kyaterekera study between June 2019 and March 2020. Women were eligible for the study if they: (1) were age 18 or over; (2) reported engagement in transactional sex (a sex act in exchange for pay) in the past 30 days; and (3) reported engagement in one or more episodes of unprotected sex in the past 30 days. Women completed a baseline assessment, were tested for HIV and other sexually transmitted infections (STIs) at enrollment, and were connected with antiretroviral therapy (ART), STI treatment, or PrEP, based on need and interest. Descriptive statistics examined baseline data on PrEP acceptability and initiation. Independent variables (i.e. years in sex work, recent sexual coercion, perceived HIV and sex work stigmas, harmful alcohol use, barriers to medical care, and social support) were derived from the empirical literature and women's self-report. Bivariate analysis was performed to test associations between main effects of these variables. Using binomial logistic regression, predictive models were evaluated for two distinct outcomes—PrEP acceptability and PrEP initiation/uptake. Findings: At baseline, 59% of women ( n  = 322) tested HIV negative. Among WESW testing negative, 11% ( n  = 36) were already PrEP enrolled. Most women reported willingness to use PrEP ( n  = 317; 91%). Slightly over half of WESW not already on PrEP agreed to initiate PrEP ( n  = 158; 55%). Logistic regression models demonstrate that acceptability of or willingness to use PrEP was significantly associated with fewer years engaged in sex work (AOR= ·18, 95% CI 0·05-·66, p <·01) and greater perceived social support from family (AOR= 1·39, 95% CI 1·03 -1.88, p <·05). PrEP initiation was negatively associated with greater perceived social support from friends (AOR=·81, 95% CI ·68–0·97, p <·05) and positively associated with higher perceived stigma due to sex work among family members (AOR=2·20, 95% CI 1·15–4·22, p <·05). Interpretation: Despite endorsing PrEP use, many WESW remain reluctant to use it. This gap in prevention practice highlights the heart of a failing PrEP prevention cascade. Findings point to the important role family and friend support may play in destigmatizing sex work and PrEP use for women. Social and structural-level efforts are needed to improve educational messaging and to integrate positive messaging into health promotion campaigns for women and their families, while also working toward decriminalizing sex work. Funding: This paper was made possible with funding from United States National Institute of Mental Health (Grant number: R01MH116768).